UiO-66 metal organic framework nanoparticles loaded carboxymethyl chitosan/poly ethylene oxide/polyurethane core-shell nanofibers for controlled release of doxorubicin and folic acid - Farboudi, Amirnezam; Mahboobnia, Khadijeh; Chogan, Faraz; Karimi, Mahsa; Askari, Anis; Banihashem, Solmaz; Irani, Mohammad (Elsevier, 2020)
Doxorubicin (DOX) and folic acid (FA) were incorporated into the UiO-66 metal organic framework (MOF) and following were loaded into the carboxymethyl chitosan/poly ethylene oxide (PEO)/polyurethane core-shell nanofibers for controlled release of DOX and FA toward MCF-7 cells death. The synthesized nanocarriers were characterized using TEM, XRD, and SEM analysis. The drug loading efficiency and release profiles of DOX/MOF and FA/MOF from synthesized nanofibers have been investigated. The fitting of kinetic data by the pharmacokinetic models demonstrated the non-Fickian diffusion from nanofibers and Fickian diffusion from core-shell fibers. The cytotoxicity of synthesized nanofibers toward MCF-7 cancer cells was evaluated using DAPI staining, MTT assay and flow cytometry tests to investigate the simultaneous use of DOX and FA in the nanofibrous matrix for MCF-7 cells death in vitro. The maximum cell death using DOX-FA loaded-core-shell fibers produced by coaxial electrospinning method under 0.3, 0.5 and 0.8 mLh(-1) shell flow rates were found to be 82 +/- 0.7, 83 +/- 0.5 and 87 +/- 0.5% after 168, 240 and 240 h, respectively. The cytotoxicity results indicated that the co-delivery of DOX and FA into the core-shell fibers could be widely used for various cancers treatment. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Carboxymethyl chitosan; UiO-66 metal organic framework; Core-shell nanofibers; Doxorubicin; Folic acid